Assessment of physical fatigability and fatigue perception in myasthenia gravis. Issue 5 (6th January 2017) - Jordan, Berit; Mehl, Theresa; Schweden, Tabea L.K.; Menge, Uwe; Zierz, Stephan
ABSTRACT: Introduction: Fatigue includes both performance fatigability and fatigue perception. Methods: In 32 stable patients with generalized myasthenia gravis (MG) and 17 controls, time‐dependent physical performance was assessed by the arm movement test (AMT) and 6‐minute walk test (6MWT). MG patients presented with low quantitative MG scores (mean 0.5, SD 0.5) and without pathologic decrement. Fatigability was based on calculation of linear trend (LT) reflecting dynamic performance within subsequent constant time intervals. Perception of physical fatigue was analyzed using fatigue questionnaires. Results: MG patients showed a negative LT in both AMT and 6MWT, significantly differing from stable performance in controls. LT inversely correlated with elevation of acetylcholine receptor antibodies ( r  = −0.59, P  < 0.005) but not with quantitative MG score and fatigue perception. Conclusions: LT allows quantification of fatigability as an objective measurement of decline in individual performance, even in patients without obvious neuromuscular deficits in routine testing. The missing correlation of experienced fatigue supports the multidimensional fatigue model. Muscle Nerve 55: 657–663, 2017